1.
\frac{4x+1}{12} |*12 " alt="\frac{x-3}{4}>\frac{4x+1}{12} |*12 " align="absmiddle" class="latex-formula">
4x+1" alt="3x-9>4x+1" align="absmiddle" class="latex-formula">
9+1" alt="3x-4x>9+1" align="absmiddle" class="latex-formula">
10" alt="-x>10" align="absmiddle" class="latex-formula">
(A)
2.
![|\frac{63}{x}|-1=43,2:2,16 |\frac{63}{x}|-1=43,2:2,16](https://tex.z-dn.net/?f=%7C%5Cfrac%7B63%7D%7Bx%7D%7C-1%3D43%2C2%3A2%2C16)
![|\frac{63}{x}|-1=20 |\frac{63}{x}|-1=20](https://tex.z-dn.net/?f=%7C%5Cfrac%7B63%7D%7Bx%7D%7C-1%3D20)
![\frac{63}{|x|}=21 \frac{63}{|x|}=21](https://tex.z-dn.net/?f=%5Cfrac%7B63%7D%7B%7Cx%7C%7D%3D21)
![|x|=63:21 |x|=63:21](https://tex.z-dn.net/?f=%7Cx%7C%3D63%3A21)
![|x|=3 |x|=3](https://tex.z-dn.net/?f=%7Cx%7C%3D3)
(A)
3.
![\frac{32}{3-\frac{1}{3-\frac{3}{3-\frac{1}{3-\frac{1}{3}}}}}=\frac{32}{3-\frac{1}{3-\frac{3}{3-\frac{3}{8}}}}=\frac{32}{3-\frac{1}{3-\frac{3*8}{21}}}=\frac{32}{3-\frac{21}{63-24}}=\frac{32}{3-\frac{21}{39}}=\frac{32}{3-\frac{7}{3}}= \frac{32}{3-\frac{1}{3-\frac{3}{3-\frac{1}{3-\frac{1}{3}}}}}=\frac{32}{3-\frac{1}{3-\frac{3}{3-\frac{3}{8}}}}=\frac{32}{3-\frac{1}{3-\frac{3*8}{21}}}=\frac{32}{3-\frac{21}{63-24}}=\frac{32}{3-\frac{21}{39}}=\frac{32}{3-\frac{7}{3}}=](https://tex.z-dn.net/?f=%5Cfrac%7B32%7D%7B3-%5Cfrac%7B1%7D%7B3-%5Cfrac%7B3%7D%7B3-%5Cfrac%7B1%7D%7B3-%5Cfrac%7B1%7D%7B3%7D%7D%7D%7D%7D%3D%5Cfrac%7B32%7D%7B3-%5Cfrac%7B1%7D%7B3-%5Cfrac%7B3%7D%7B3-%5Cfrac%7B3%7D%7B8%7D%7D%7D%7D%3D%5Cfrac%7B32%7D%7B3-%5Cfrac%7B1%7D%7B3-%5Cfrac%7B3%2A8%7D%7B21%7D%7D%7D%3D%5Cfrac%7B32%7D%7B3-%5Cfrac%7B21%7D%7B63-24%7D%7D%3D%5Cfrac%7B32%7D%7B3-%5Cfrac%7B21%7D%7B39%7D%7D%3D%5Cfrac%7B32%7D%7B3-%5Cfrac%7B7%7D%7B3%7D%7D%3D)
(A)